Changed Tendencies in Research Issues on Motivation for Foreign Languages Learning (Review for 2021) - Tsalikova, I.K.; Pakhotina, S.V.; Kungurova, I.M.; Slizkova, E.V.; Voronina, E.V. (Psihologo-pedagogičeskie issledovaniâ, 2022)
The COVID-19 pandemic has changed social and educational environment, which affected the educational process participants and the research directions. The article shows the changes in the direction of studies dealing with the issues of university students` foreign languages learning motivation, published in 2021. Researching is still aimed at studying the online environment and its potential. Its high potential to develop the motivation is stated, but the lack of participants` experience of its using prevents its full acceptance so far. The problems of maintaining personal interaction between a teacher and students; overcoming stress and anxiety; adaptation to the virtual learning environment and their impact on the motivation are of research interest. Another part of the research works is traditionally devoted to the components of educational motivation, strategies for their managing, etc. The results of the analysis will help to understand how well the problem has been studied and determine the direction of future research. Пандемия COVID-19 изменила условия предоставления образовательных услуг, что сказалось на субъектах и объектах образовательного процесса и на векторах исследовательского интереса. В статье прослеживается изменение направлений научных исследований, посвященных мотивации изучения иностранных языков у студентов вузов, в 2021 году. Результаты показывают, что большая часть исследований связана с изучением онлайн-среды и ее потенциала. Констатируются ее высокие потенциальные возможности для развития мотивационной сферы, однако недостаточный опыт их использования пока препятствует полному принятию. Интерес вызывают проблемы поддержания личного взаимодействия преподавателя и студентов; преодоление стресса, тревожности; адаптация к виртуальной среде обучения и ее влияние на мотивацию. Другая часть работ традиционно посвящена компонентам учебной мотивации и ее развитию. Результаты анализа помогут понять степень изученности данной проблемы и определить направление исследований в будущем.